Orderly Self-Stacking a High-Stability coating of MXene@Polydopamine hybrid onto textiles for multifunctional personal thermal management. (September 2022) - Yan, Biaobiao; Zhou, Man; Yu, Yuanyuan; Xu, Bo; Cui, Li; Wang, Qiang; Wang, Ping
Graphical abstract: Highlight: A multifunctional textile integrating solar, Joule and low-radiation heating was successfully prepared by an easy-to-operate method. The MXene@PDA hybrid coatings are orderly self-stacked on the fabric surface with high conductivity and self-cleaning properties. The MXene@PDA decorative multifunctional textile showing excellent antioxidation, long-term durability and environmental stability. Abstract: In this work, a hybrid coating of mussel-inspired dopamine and MXene was successfully prepared, and deposited on the cotton fabric surface uniformly to construct a multifunctional textile. Depending on the unique adhesion of polydopamine (PDA), the MXene coating is orderly self-stacked on the fabric surface with antioxidation and a high conductivity close to 300 S/m, further hydrophobic modification endows the fabric with excellent self-cleaning ability. Subsequently, a personal thermal management system consisting of solar, Joule and low-radiation heating components that can switch modes flexibly according to the scenario is constructed, which facilitates the wearable warm fabric to cope with complex environments. Meanwhile, the MXene@PDA-decorated fabric provides electromagnetic interference (EMI) shielding efficiency of exceeding 55 dB and thermal camouflage ability. With an easy-to-operate preparation process, long-time durability, MXene@PDA-decorated fabric exhibit great potential for manufacturing flexible, wearable, multifunctional personal precision thermal management textile devices.